IMPLEMENTATION OF THE OPERATIONAL CURRICULUM OF EDUCATIONAL UNITS IN THE APPLICATION OF CHARACTER VALUES AT STATE ELEMENTARY SCHOOL 3 ULIM, PIDIE JAYA REGENCY - Sentia, Zulfa; Bahri, Saiful; Mulyadi, Said (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
The purpose of this study is to describe the planning, implementation and supervision of the implementation of the operational curriculum of educational units in the application of character values ​​at State Elementary School 3 Ulim.The method used is a descriptive qualitative research method with research instruments in the form of observation, interviews and documentation. This method is used to observe the implementation of the Educational Unit Operational Curriculum (KOSP) at SD Negeri 3 Ulim. The respondents interviewed were the principal, vice principal for curriculum, homeroom teacher and several subject teachers. Data analysis techniques were carried out by means of data reduction, data presentation, drawing conclusions and data verification. The results of the study indicate that the implementation of the Educational Unit Operational Curriculum (KOSP) at SD Negeri 3 Ulim was carried out through planning that included analysis of the characteristics of the educational unit and the preparation of a vision, mission, objectives, and learning plans that were in accordance with student needs. The implementation of the curriculum focuses on student-centered learning, adjusted to their developmental stages and characteristics, and supported by collaboration between teachers. Supervision is carried out through the application of relevant teaching modules, technical assistance to teachers, and the involvement of all stakeholders in supporting the success of the curriculum implementation. The results of the implementation of the Educational Unit Operational Curriculum which was carried out in accordance with systematic planning and supervision were successfully implemented at SD Negeri 3 Ulim, Pidie Jaya Regency. This study contributes to the implementation of KOSP at the elementary school level by emphasizing the integration of student characteristic analysis, collaboration between teachers, and comprehensive stakeholder involvement in every stage of curriculum planning, implementation, and supervision.